PERENCANAAN PENCEGAHAN KEJENUHAN AKADEMIK DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMA PLUS PAGELARAN SUBANG - Gifary, Arie; Najmul Hidayat, Ayi; Srihandayani, Srihandayani; H Soro, Suharyanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Academic burnout is a significant issue that can hinder students' motivation to learn, particularly in educational institutions with intense activities such as SMA Plus Pagelaran, which implements a pesantren-based school system. The dense series of learning and pesantren activities, long routines requiring high focus, and ongoing academic pressures encourage the emergence of symptoms of emotional exhaustion, decreased interest in learning, and low student engagement in the learning process. This situation indicates the need for structured prevention planning to maintain students' psychological well-being and motivation to learn. This study aims to identify the forms of academic burnout experienced by students, examine the prevention planning strategies developed by the school, and explain how these strategies impact learning motivation. The study used a qualitative approach with a descriptive design. The research findings indicate that students experience academic burnout in the form of emotional exhaustion, boredom with routines, difficulty maintaining focus, and weak learning motivation. To address this, SMA Plus Pagelaran developed a prevention plan that included rearranging the school-pesantren schedule, implementing activity-based learning, strengthening preventive counseling, and providing interest and talent programs as a means of refreshing students. This planning contributes significantly to increasing learning motivation, as seen from the increased enthusiasm, participation, and readiness of students to participate in academic activities.